2009
DOI: 10.1111/j.1468-2982.2008.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Prophylactic Treatments of Migraine Lower Plasma Glutamate Levels

Abstract: The role of glutamate in migraine treatment has not been much studied, even if this amino acid seems to be crucial in the pathogenesis of migraine. Our aim was to determine if there were differences in the plasma levels of glutamate between migraine patients and control subjects and if plasma levels of glutamate in migraine patients modified after 8 weeks of prophylactic treatment. We studied 24 patients with diagnosis of migraine without aura according to International Classification of Headache Disorders, 2n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 41 publications
4
52
0
Order By: Relevance
“…In blood from interictal episodic migraine patients the pooled difference was not statistically significant (SMD: 1.08, 95% CI: -0.07, 2.22) (56)(57)(58)(59)(60)(61)(62). After exclusion of paediatric migraine patients (58), glutamate concentrations were increased in the (24).…”
Section: Glutamate (Figure 2)mentioning
confidence: 93%
“…In blood from interictal episodic migraine patients the pooled difference was not statistically significant (SMD: 1.08, 95% CI: -0.07, 2.22) (56)(57)(58)(59)(60)(61)(62). After exclusion of paediatric migraine patients (58), glutamate concentrations were increased in the (24).…”
Section: Glutamate (Figure 2)mentioning
confidence: 93%
“…Elevated glutamate levels in the cerebrospinal fluid were measured during attacks in migraineurs, supporting the hypothesis of neuronal hyperexcitability in the disorder [122], and research data indicate that glutamate antagonists might be effective against the aura in FHM [123]; there are also observations regarding their usefulness in abolishing headache [124]. Topiramate a well-known glutamate antagonist, is effective in migraine prophylaxis [125] and any different effective prophylactic treatments lower the plasma glutamate level [126]. CSD, a hallmark of migraine aura, can also induce cytotoxic cell damage via glutamatergic mechanisms [118], leading to neuronal necrosis.…”
Section: Connection Between Migraine and Strokementioning
confidence: 95%
“…It has been found that mean baseline fasting plasma glutamate in 24 episodic migraine headache without aura patients was ~60 M as compared with ~ 10 M in 24 age and sexmatched controls [35] . Patients fasting plasma glutamate levels were reassessed 8 weeks after initiation of a migraine prophylactic therapy (topiramate, propranolol, amitriptyline, or flunarizine).…”
Section: Can Dietary Restriction Of Msg Affect Chronic Pain Conditions?mentioning
confidence: 98%
“…Multiple reports show that blood and salivary glutamate levels are elevated by 25-600% in migraine patients compared to healthy controls [31][32][33][34][35]. In addition, there is some evidence that glutamate levels in platelets are elevated in chronic tension-type headache sufferers [32].…”
Section: Can Dietary Restriction Of Msg Affect Chronic Pain Conditions?mentioning
confidence: 99%